Rola handlu w zaopatrzeniu produkcyjnym rolnictwa - Brojerski, Marek (Wydział Prawa i Administracji UAM, 1977)
The purpose of the present considerations was to determine the role of trade of articles for agricultural production, its conditions and the directions of changes. The main thesis of these considerations was the statement that the organization of trade of articles for agricultural production is not a spontaneous phenomenon, but it depends on the conditions of its activities — and therefore it is indirectly dependant on the economic level of agriculture. The problem resolves itself into observing the effects of the influence of the different economic levels of agriculture on the activities of trade of articles for agricultural production. A lot of attention is paid to determining the directions of development of trade of articles for argicultural production. It is impossible to realize stimultaneously all the factors which make it difficult for us to determine the role of trade in the field of circulation of supplies for agriculture. At the present moment the speed and the scale of the socio-economic changes in agriculture are unknown. The experience of trade of these articles when there exists a full satisfaction of productive needs of agriculture is too small. Nevertheless, we may assume that the situation of creating big farms and developing direct commodities circulation industry-farms there are possibilities of goods traffic excluding the rural trade network.
The Role of Trade in Supplies for Agriculture